Milestones in contraceptive vaccines development and hurdles in their application - Gupta, Satish Kumar (Hum Vaccin Immunother, 2013)
Contraceptive vaccines have been proposed for controlling the growing human population and wildlife population management. Multiple targets such as gonadotropin releasing hormone (GnRH), luteinizing hormone, follicle stimulating hormone, gonadotropin receptors, sperm-specific proteins and zona pellucida glycoproteins have been exploited to develop contraceptive vaccine and their efficacy investigated and shown in various experimental animal models. Vaccines based on GnRH have found application in immuno-castration of male pigs for prevention of boar-taint. Vaccines based on zona pellucida glycoproteins have shown promising results for population management of wild horses and white-tailed deer. Phase II clinical trials in women with β-human chorionic gonadotropin (β-hCG)-based contraceptive vaccine established proof of principle that these can be developed for human application. Block in fertility by β-hCG contraceptive vaccine was reversible. Further research inputs are required to establish the safety of contraceptive vaccines, improve their immunogenicity and to develop novel vaccine delivery platforms for providing long lasting immunity.